\(\frac {2}{3}\) + \(\frac {3}{4}\) =
\(\frac {1}{4}\) + \(\frac {2}{3}\) =
\(\frac {1}{2}\) + \(\frac {3}{4}\) =
\(\frac {1}{2}\) + \(\frac {1}{3}\) =
\(\frac {2}{3}\) + \(\frac {1}{2}\) =
\(\frac {1}{3}\) + \(\frac {3}{4}\) =
\(\frac {3}{4}\) + \(\frac {1}{5}\) =
\(\frac {2}{5}\) + \(\frac {1}{3}\) =
\(\frac {2}{5}\) + \(\frac {1}{2}\) =
\(\frac {1}{3}\) + \(\frac {1}{5}\) =
\(\frac {2}{3}\) + \(\frac {3}{5}\) =
\(\frac {3}{5}\) + \(\frac {1}{3}\) =
\(\frac {3}{5}\) – \(\frac {1}{3}\) =
\(\frac {2}{3}\) – \(\frac {1}{4}\) =
\(\frac {3}{4}\) – \(\frac {2}{3}\) =
\(\frac {3}{4}\) – \(\frac {1}{2}\) =
\(\frac {1}{2}\) – \(\frac {1}{3}\) =
\(\frac {2}{3}\) – \(\frac {1}{2}\) =
\(\frac {3}{4}\) – \(\frac {1}{3}\) =
\(\frac {3}{4}\) – \(\frac {1}{5}\) =
\(\frac {2}{5}\) – \(\frac {1}{3}\) =
\(\frac {1}{2}\) – \(\frac {2}{5}\) =
\(\frac {1}{3}\) – \(\frac {1}{5}\) =
\(\frac {2}{3}\) – \(\frac {3}{5}\) =
Created by Ulises Yo Soy
over 2 years ago

